Uniformidade de irrigação por gotejamento usando efluente tratado de abatedouro de aves - Morais, James (2018)
The processes that take part of poultry slaughter are responsible for a great amount of water consumption and, consequently, a generation of large volumes of wastewater, which are usually disposed on soil without any control of uniformity regarding its distribution. Thus, this study aimed at evaluating a drip irrigation system, applied to dispose treated poultry slaughterhouse effluent on soil, using three effluent application rates of 100, 200 and 300 m³ ha-1 day-1. Besides the irrigation system, the effluent quality was also evaluated according to its physical-chemical characteristics. The evaluation of the results was given by the following coefficients: Christiansen Uniformity (CUC), Uniform Distribution (UDC), the Statistical Uniformity Coefficient (SUC) as well as quality control techniques. This trial was carried out in an eucalyptus reforestation area from the Industrial Poultry Slaughterhouse of Lar Agroindustrial Cooperative, in Matelândia city, PR. According to data obtained in this research, it was concluded that drip irrigation system, using the proposed rates, can be considered adequate, since it has shown uniformity in distribution of flows, pH and electrical conductivity. For pH and electrical conductivity, all the evaluated uniformity coefficients, CUC, UDC and SUC, were estimated in more than 90% and considered excellent. For the flow rates, all the coefficients were estimated as superior to 90% for 100 m³ ha-1 day-1 treatment and above 80% for treatments of 200 and 300 m³ ha-1 day-1. Usually, the distributions showed the highest coefficient of uniformity for the three parameters evaluated in the three studied treatments, for the highest tested rate of application. Regarding the effluent characterization, it was concluded that its main characteristics are the concentrations of nitrogen, phosphorus and carbon. And during the experiment, the industry kept the standards of disposal in the environment, which were determined by the environmental agencies. Finally, it was concluded that the statistical process control is adequate to evaluate the effluents as well as irrigation uniformity in tests area.